Functional diversity of an evergreen forest ecosystem of Vazhachal forest division, Kerala - Deepakkumar R (Department of Forest Management and Utilisation, College of Forestry, 2016)
The present study was carried out at Sholayar forest range of Vazhachal forest division of Thrissur district, Kerala state. The main objective of the study was to enumerate the species and functional diversity of selected aboveground and belowground biological components of this forest ecosystem. The study also aimed to understand the links between diversity, soil aspects, and functioning of the tropical west coast wet evergreen forest ecosystem. Five 0.1 ha (31.62 m x 31.62 m) sample plots were randomly laid in the selected grids in the Vazhachal forests as per the guidelines of National Working Plan Code 2014. A total of 175 plant species (<10 cm GBH) were recorded from the 0.5 ha (0.1 x 5 nos.) area in which 57 recruits, 29 shrubs, 28 herbs, 19 climbers, 14 pteridophytes, 13 polypores, 7 epiphytes, 4 orchids and 4 bryophytes. Palaquium ellipticum, Cullenia exarillata and Mesua ferrea are well represented young recruits. In addition, Dendrocnide sinuata, Psychotria nudiflora and Strobilanthus species were observed as dominant in the shrubby layer. Curcuma neilgherrensis, Pellionia heyneana and Oplismenus compositus are some of the herbs found in the herbaceous layer. Coscinium fenestratum, Leea indica, and Calamus species are the some of the important climbers found in the sampled sites. A total of 84 tree species were recorded from the 0.5 ha area with 1093 individuals per hectare and basal area of 85.43m2. Aglaia barberi, Cullenia exarillata, Mesua ferrea and Palaquium ellipticum were the dominated in the top canopy. Dipterocarpus indicus, Hydnocarpus pentandra and Myristica beddomei were observed in the middle storey. Garcinia wightii, Spondias pinnata and Strychnos nux-vomica were occupied in the lower canopy. Euphorbiaceae, Clusiaceae and Meliaceae were the dominant tree families. The diameter frequency as well as height frequency distribution of the sampled sites showed the reverse J shaped curve which reflects the healthy population structure. Margalef richness index (28.31), Shannon-Wieners index (4.08), Simpson index (0.9808) and Pielou`s index (0.6587). Rényi’s diversity profile and Principal Component analysis shows that there is smaller variation across sampled sites. The dominating plant functional traits are evergreen plant type (70.2%), simple leaf type (72.6%), glabrous textured leaf type (78.57%), smooth textured bark type (47.2%), medium thick bark type (53.5%), capsule fruit type (32.1%) and zoochory type (55.95%) of fruit dispersal which are typical of a tropical evergreen forest ecosystem. A total of 870 individuals of soil invertebrates under 28 different order were obtained from the 0.5 ha area. Isoptera, Hymenoptera and Coleoptera emerged as the dominant orders. Shannon- Wiener Index (2.40), Simpson Index of diversity (0.14) and Pielou's evenness Index (0.51) are soil invertebrates’ diversity. The population of Bacteria (44.4 x 106 cfu g-1), Fungi (26.3 x 103 cfu g-1), Fluorescent pseudomonads (18.3 x104 cfu g-1), Nitrogen fixers (14.4 x 104 cfu g-1), Actinomycetes (16.4 x 104 cfu g-1) and Phosphate solubilizers (20 x 103 cfu g-1). Soil temperature (19.82˚C), Bulk density (1.28g cm-3), Moisture content (29.06%), Sandy loam soil (Sand- 78.15%, Silt- 16.04% and Clay- 5.82%), Organic carbon (4.19%), Soil acidity (5.25) and Soil electrical conductivity (0.07mSm-1) are recorded during the study.